Self-help group therapy interventions for self-harm in adolescents - Setia Purbaningrum; Muhammad Ari Arfianto; Ajeng Pramudianingtias; Sefira Khoirotus Salsa; Amelia Wulan Sari; Rafika Azzahra Salsabila Utomo; Al Mar’atul Ahlak (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Adolescents who are unable to manage negative emotions are more likely to engage in self-harm. Alternative management that can be applied to reduce self-harm symptoms in adolescents is self-group therapy. Purpose: To determine the effectiveness of self-help group therapy in reducing self-harm symptoms in adolescents. Method: A quantitative approach, specially focusing on pre-experimental one-group pretest-posttest method. The study took place from June 2023 in Junior High Schools, Malang. The independent variable was self-help group therapy dependent variable is self-harm symptoms. Using total sampling, 70 respondents were selected who met specific inclusion and exclusion criteria. The analysis proceeded with a univariate test to determine the frequency distribution of respondent’s characteristics, followed by bivariate analysis using paired sample t-test. Results: Self-harm symptoms before the administration of self-help group therapy showed a minimum score of 40 and a maximum score of 79, with a mean score of 58.16. After the implementation of self-help group therapy, the self-harm symptom scores decreased, ranging from a minimum of 22 to a maximum of 67, with a mean score of 36.51. Conclusion: Self-help group therapy has been shown to significantly reduce self-harm symptoms in adolescents. This is evidenced by a notable decrease in the average self-harm score following the intervention, compared to the score prior to receiving self-help group therapy.